The effect of mobile personalised texting versus non-personalised texting on the caries risk of underprivileged adults: a randomised control trial - Makiko Nishi; Virginia Kelleher; Michael Cronin; Finbarr Allen (BMC, 2019)
Abstract Background In the Republic of Ireland (RoI), fluoridation has been effective and efficient for caries prevention at population level, regardless of income status; however, at individual level it still has limitations. This study aimed to compare personalised versus non-personalised text messaging on 'chance of avoiding new cavities' with the Cariogram, a computer-based caries risk assessment (CRA) model, in an economically disadvantaged adult population in the RoI. Methods The intervention was via a CRA summary letter plus 24 weekly personalised mobile-phone short text messages (text messages) based on the individual's CRA, compared with a non-personalised approach via a non-personalised letter and a predetermined, fixed set of 24 weekly text messages. The study was designed as a two-arm parallel-group, single-blinded (assessor), randomised controlled study in County Cork, RoI. The primary outcome was a comparison of 'chance of avoiding new cavities' calculated by the Cariogram with clinical examination, interview, CRT® (Ivoclar Vivadent, Liechtenstein) and three-day food diary between the two groups at follow-up. We combined stratified randomisation with blocked randomisation for 171 participants who completed baseline. Of them, 111 completed follow-up and were analysed (56 and 55 from the personalised and non-personalised groups, respectively). Due to protocol violations, both intent-to-treat (ITT) and per-protocol analyses were conducted. Results The ITT analysis did not show a personalised intervention effect on 'chance of avoiding new cavities'. Of the secondary outcome measures, only the stimulated saliva flow factor showed a personalised intervention effect, p = 0.036, OR = 0.3 (95% CI = 0.1, 0.9). The per-protocol analysis with 21 personalised and 33 non-personalised participants within two-message deviations showed no significant effect on 'chance of avoiding new cavities'. Conclusions The null hypothesis in regard to the primary outcome for both ITT and per-protocol analyses was not rejected; however, as the minimal clinically important difference was included in the 95% CI for the per-protocol analysis, replication studies will be worth conducting to explore the potential of mobile devices for individual caries risk reduction. Trial registration University Hospital Medical Information Network Clinical Trials Registry (UMIN000027253) on 10 May 2017. The study was retrospectively registered.